The Effect of Audit Quality, Tax Planning and Leverage on Earnings Management - Dwianika, Agustine; Wisnantiasri, Sila (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
This study is to address a current issues abouthow important of audit quality for supporting firm’sperformance, due still there a research gap from previousliteratures about the effects of audit quality on earningsmanagement. This paper aims to illustrate and examine theeffect of audit quality on the relationship of tax planningrates and leverage on earnings management, based onevidence in Indonesia. This quantitative study usingsecondary data obtained from the company's annual report.The research population is LQ-45 firms listed on theIndonesia Stock Exchange in 2013-2017 as many as 45companies. The data analysis technique used was multiplelinear regression analysis using SPSS 22 for Windows. Theresults of this study indicate that tax planning and leverageaffect earnings management. While audit quality as amoderating variable strengthens the relationship betweentax planning and leverage on earnings management. Thisstudy provides futher evidence of earnings managementrelated about audit quality, tax planning and leverageseparately for academically side. For practitioners, it can beused as a consideration in making investment decisions, thatthere is a connection between the things that becomevariables in this study.